2021
DOI: 10.1111/asap.12285
|View full text |Cite
|
Sign up to set email alerts
|

Association of public explanations of why children struggle and support for policy solutions using a national sample

Abstract: Purpose Despite evidence showing the importance of structural determinants for child well‐being and the existence of policies that can promote child well‐being, many communities are not adopting these policies. Limited awareness of structural determinants may explain this gap. This study establishes the public's recognition of structural determinants and their associations with support for policies that promote child well‐being. Methods Secondary analyses of survey data collected in 2019 from a random sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Research has found that when people understand the societal cause of an issue, such as substance use or childhood adversity, they are more likely to support policy solutions (Klevens et al, 2021). For example, those who recognize the role of economic conditions or access to high‐quality education in the current overdose epidemic are more likely to support more equitable economic or educational policies (e.g., increased minimum wage, increased access to high‐quality early childcare), whereas those who focus on individual factors that lead to substance use are more likely to focus on criminal justice or therapeutic responses.…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that when people understand the societal cause of an issue, such as substance use or childhood adversity, they are more likely to support policy solutions (Klevens et al, 2021). For example, those who recognize the role of economic conditions or access to high‐quality education in the current overdose epidemic are more likely to support more equitable economic or educational policies (e.g., increased minimum wage, increased access to high‐quality early childcare), whereas those who focus on individual factors that lead to substance use are more likely to focus on criminal justice or therapeutic responses.…”
Section: Introductionmentioning
confidence: 99%